Banking regulation and market making - Cimon, David; Garriott, Corey (Journal of Banking & Finance, 2019)
We model how securities dealers respond to regulations on leverage, position, and liquidity such as those imposed by the Basel III framework. The dealers respond by endogenously moving to make markets on an agency basis, matching buyers to sellers rather than taking client positions on the balance sheet. Agency-based market making creates a cost-risk tradeoff in which investor welfare declines but dealers become less risky. The costs to investors do not show up in all liquidity metrics: While asset prices exhibit greater price impact, bid-ask spreads do not change and trading volumes can even increase, which can help explain the varying findings from the empirical literature.